Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1029/2021jd036114
|View full text |Cite
|
Sign up to set email alerts
|

Dust Activities Induced by Nocturnal Low‐Level Jet Over the Taklimakan Desert From WRF‐Chem Simulation

Abstract: Nocturnal low-level jet (NLLJ) is the wind speed maximum occurring near the top of the night boundary layer with strong wind shear and pronounced diurnal variation (Blackadar, 1957;Rife et al., 2010;Van de Wiel et al., 2010). Various mechanisms for the development of NLLJ have been identified, including the topographic thermal and dynamic forcing, coupling with upper atmospheric jets, synoptic system forcing, and positive feedback from diabatic heating (Holton, 1967;Kahl, 1990;Stensrud, 1996). Among them, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 91 publications
0
5
0
Order By: Relevance
“…Xiao, Zhou, and Liao [37] suggested that strong winds are the direct cause of dust storms in the Taklimakan region, based on site observation data. Additionally, if the surface sensible heat flux increases, the near-surface air temperature rises, which increases the near-surface turbulence and makes the air instability increase, which is conducive to the strengthening and persistence of dust weather [46,47,72,73]. In this study, we examined three primary factors influencing dust emission and investigated the differences between the SDAP and SDIP (Figure 5).…”
Section: Near-surface Meteorological Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Xiao, Zhou, and Liao [37] suggested that strong winds are the direct cause of dust storms in the Taklimakan region, based on site observation data. Additionally, if the surface sensible heat flux increases, the near-surface air temperature rises, which increases the near-surface turbulence and makes the air instability increase, which is conducive to the strengthening and persistence of dust weather [46,47,72,73]. In this study, we examined three primary factors influencing dust emission and investigated the differences between the SDAP and SDIP (Figure 5).…”
Section: Near-surface Meteorological Factorsmentioning
confidence: 99%
“…Additionally, anomalous largescale environment conditions related to the Arctic Oscillation (AO) and El Nino-Southern Oscillation (ENSO) can create favorable conditions for the enhanced dust activities in Asia [42][43][44][45]. However, the regulation of summer dust activity in the TD by large-scale circulation has received less attention, apart from the contribution of momentum transfer of the nocturnal low-level jet [46,47].…”
Section: Introductionmentioning
confidence: 99%
“…In similar respects, Cheng et al (2022) simulated the role of topography driving low-level wind convergence, and thereby enhancing heat fluxes and convection. Atmospheric transport and coupling to surface and hydrological processes also played a role in dust transport and emission (Han et al, 2022) and influencing stream outflow (Getirana et al, 2021).…”
Section: A Scale For All Silosmentioning
confidence: 99%
“…LLJs in hot desert areas are usually NLLJs, although a fraction of the LLJs are connected to convective cold pools (Heinold et al, 2013). LLJs in hot deserts have strong implications for forming dust storms (Fiedler et al, 2013;Z. Han et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…LLJs in hot desert areas are usually NLLJs, although a fraction of the LLJs are connected to convective cold pools (Heinold et al., 2013). LLJs in hot deserts have strong implications for forming dust storms (Fiedler et al., 2013; Z. Han et al., 2022). Likewise, LLJs happening in continental polar regions (PLLJs), or cold deserts, are generated by the stabilization of the atmospheric boundary layer via near‐surface cooling or warm air advection (Heinemann & Zentek, 2021).…”
Section: Introductionmentioning
confidence: 99%